Primary Malignant Fibrous Histiocytoma: A Rare Case. (18th October 2011) - Katsourakis, Anastasios; Noussios, George; Hadjis, Iosif; Evangelou, Neofitos; Chatzitheoklitos, Efthimios
Abstract : Malignant fibrous histiocytoma (MFH) of the small intestine is an extremely rare condition. It occurs most commonly in the extremities and the trunk. We report a case of a 67-year-old woman who admitted with fever, myalgia, and altered status. After thorough investigation, a tumor of the jejunum was found. The patient underwent complete surgical removal of the tumor. A diagnosis of MFN (undifferentiated high-grade pleomorphic sarcoma) was made. The patient received adjuvant chemotherapy with Gemcitabine. Two years after the operation, the patient died due to recurrence of the disease. MFH of the small intestine is an extremely rare neoplasm with an aggressive biological behaviour. In this paper, pathogenesis, natural history, and treatment are reviewed.